DAIF AND SCP – DERIVATIONS ON SEMIGROUP IDEAL I OF A NEAR–RING N. - Majeed, A H; Abdulla, Hiba (Al-Nahrain Journal of Science, 2010)
In this paper we study two kinds of derivations on a semigroup ideal I of a near ring N. Thefirst kind called Daif derivation (Daif 1 derivation and Daif 2 derivation), the second kind iscalled strong commutativity preserving derivations. Bell and Mason, showed that a prime nearring N must be commutative if it admits any of these kinds of derivations, and we generalize this toa semigroup ideal I.